2018
DOI: 10.1093/jas/sky421
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crossbreeding on meat goat doe fitness when comparing Boer F1 with base breeds in the Southeastern United States1

Abstract: Understanding fitness level among various breeds is essential for sustainable meat goat production. Research on the relative fitness of Boer F 1 does and straightbred base breed has been limited. Meat goat does of various genotypes (Boer, Kiko, Spanish, Boer × Kiko reciprocal F 1 crosses, and Boer × Spanish reciprocal F 1 crosses) were studied to evaluate breed effects on doe fitness traits and the expression of heterosis over 7 production years. The herd was semi-intensively managed under humid subtropical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
2
9
1
Order By: Relevance
“…Myotonic-sired goats (dams or litters) had lower ( P < 0.05) litter weights than the other breeds, while Kiko- and Spanish-sired dams produced litters with higher gross revenue values ( P < 0.05) than litters produced by Boer- and Myotonic-sired dams (data not shown). It was previously reported that the Myotonic breed is a smaller-sized meat goat than Kiko and Spanish breeds and that significant variation existed among Boer, Kiko, and Spanish does for traits similar to those recorded here ( Browning et al, 2011 ; Wang et al, 2017 ; Khanal et al, 2019 ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Myotonic-sired goats (dams or litters) had lower ( P < 0.05) litter weights than the other breeds, while Kiko- and Spanish-sired dams produced litters with higher gross revenue values ( P < 0.05) than litters produced by Boer- and Myotonic-sired dams (data not shown). It was previously reported that the Myotonic breed is a smaller-sized meat goat than Kiko and Spanish breeds and that significant variation existed among Boer, Kiko, and Spanish does for traits similar to those recorded here ( Browning et al, 2011 ; Wang et al, 2017 ; Khanal et al, 2019 ).…”
Section: Resultssupporting
confidence: 87%
“…Kids of Myotonic dams tended to be on the lower end of the weight ranges and kids of Kiko dams tended to be on the higher end of the weight ranges ( Tables 3 and 4). Breed comparisons should be viewed with some caution because this creep-feeding study was conducted across three separate mating schemes that were part of concurrent breed evaluations ( Wang et al, 2017 ; Stevens, 2018 ; Khanal et al, 2019 ). Sire and dam breeds, although managed together, were not fully represented across all three mating schemes.…”
Section: Resultsmentioning
confidence: 99%
“…Besides litter size, age, and parity number of does may affect the growth rate of kid. The growth rate of kids was higher in doe of older age (Khanal et al., 2019). Doe with higher parity number also had higher milk production (Dhara et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2019; Khanal et al . 2019). Several studies have investigated the nutritional requirements and optimal feeding mode of these animals (Paine et al .…”
Section: Figurementioning
confidence: 99%
“…Boer goat is globally recognized as one of the most ideal meat-breeding goat breeds and was originally developed from a variety of native goats in the Republic of South Africa (Malan 2000). At present, it is widely used to improve local indigenous goats and increase their economic value (Basinger et al 2019;Khanal et al 2019). Several studies have investigated the nutritional requirements and optimal feeding mode of these animals (Paine et al 2018).…”
mentioning
confidence: 99%